2020
DOI: 10.1088/1742-6596/1567/3/032096
|View full text |Cite
|
Sign up to set email alerts
|

The use of quartet card game on hydrocarbon to improve learning outcomes ten-grade students

Abstract: This study has the results of applying for a quartet media game card in student learning outcomes about Hydrocarbons in the Class X MA Darel Pekanbaru. The teacher must understand the types of media available at the school because learning with media can make it easier for students to understand subjects that are often difficult to manifest in traditional learning. One of the media created for hydrocarbon lesson material is quartet card game media because hydrocarbons are one of the chemical learning materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…The material used to explain the rules in this study were changed to a Japanese version and could be understood easily by elementary school students. It is highly possible that the Quartet Game used in this study also contributed to student motivation, as reported in a previous study 32) .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The material used to explain the rules in this study were changed to a Japanese version and could be understood easily by elementary school students. It is highly possible that the Quartet Game used in this study also contributed to student motivation, as reported in a previous study 32) .…”
Section: Discussionmentioning
confidence: 55%
“…In this study, as a result of playing the Quartet Game, we found that more than 95% of the students understood the r ules, enjoyed the game, and learned something new through playing (Tables 2 and 3, Figure 2). The rules of this game were based on the rules of quartet card games that have long been used in many countries [30][31][32][33] . The rules of the game were designed to be understood by children all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of this media considers that visual media in images will be more accessible to students, and their use does not depend on electrical energy sources. Quartet cards as learning media are unique in their competitive and exciting forms of play, so they follow the learning styles of elementary school students who still like to play new things [17]. Quartet card is a kind of game that consists of several picture cards; there is information that describes the picture.…”
Section: State Of the Art/penelitian Relevan Terdahulumentioning
confidence: 99%
“…Health education through educational games increases knowledge, attitudes, and behavior [25], [27]. Card games are educational games that are appropriate if appropriately implemented.…”
Section: Impact On Knowledge Of Hiv/aidsmentioning
confidence: 99%
“…Quartet card games improve students' knowledge comprehensively and are directed to achieve learning objectives. Quartet card games also increase students' motivation during learning [27]. In addition, students who are involved in learning through this quartet card game look more relaxed and happy [28].…”
Section: Introductionmentioning
confidence: 99%